2011
DOI: 10.1002/ijc.25484
|View full text |Cite
|
Sign up to set email alerts
|

A novel BH3 mimetic S1 potently induces Bax/Bak‐dependent apoptosis by targeting both Bcl‐2 and Mcl‐1

Abstract: Broad spectrum Bcl-2 small molecule inhibitors act as BH3 mimetics are effective antitumor agents. Herein, we have identified S1, a previously discovered small molecule Bcl-2 inhibitor, as the first authentic BH3 mimetic as well as a dual, nanomolar inhibitor of Bcl-2 and Mcl-1 (K i 5 310 nM and 58 nM, respectively). The results of fluorescence polarization assays, coimmunoprecipitation, fluorescent resonance energy transfer, and shRNA indicated that S1 can disrupt Bcl-2/Bax, Mcl-1/Bak and Bcl-2/Bim heterodime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 29 publications
1
65
0
1
Order By: Relevance
“…As such, Mcl-1 decreased. These results further illustrated our previous finding that S1-induced apoptosis is Bim-independent (16). When the accumulation was less sufficient to release Bak, as 0.05 mg/kg S1 did in vivo, no apoptosis occurred to antagonize Mcl-1 stabilization and its level was continuously increased.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As such, Mcl-1 decreased. These results further illustrated our previous finding that S1-induced apoptosis is Bim-independent (16). When the accumulation was less sufficient to release Bak, as 0.05 mg/kg S1 did in vivo, no apoptosis occurred to antagonize Mcl-1 stabilization and its level was continuously increased.…”
Section: Discussionsupporting
confidence: 89%
“…We recently showed that S1 can compete with BH3 peptide binding to Mcl-1 in vitro (16,19). It has been determined that Mcl-1 confers resistance to a promising BH3 mimetic, ABT-737.…”
Section: S1 As a Single Agent Kills Mcl-1-overexpressing Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This small-molecule inhibitor was initially suggested to be a pan-BH3 mimetic because it binds to both BCL-2 and MCL-1 (albeit with modest affinity: in the sub mmol/L range), disrupts BCL-2/BAX and MCL-1/BAK complexes, and triggers BAX/BAK-dependent apoptosis (34). A subsequent report showed that S1 does not act as a BH3 mimetic but instead induces the BH3-only protein NOXA (a specific antagonistic ligand for MCL-1) thus resulting in BAK release (15).…”
Section: S1mentioning
confidence: 99%
“…The prosurvival functions of Mcl-1 are due to interacting with proapoptotic members of the Bcl-2 family such as Bim, Bak, and Bax, and this results in the inhibition of cytochrome c release from the mitochondria and decreased apoptosis (Kazi et al, 2011;Zhang et al, 2011). Recently, it has been reported that Mcl-1 is overexpressed in tumor cells of human primary OSCC and cultured SCC cell lines, suggesting that Mcl-1 may be an important drug target for treatment of human OSCC cases (Nagata et al, 2009).…”
Section: Introductionmentioning
confidence: 99%